Differences in Anxiety and Depression by Contextual Variables in Women with Breast Cancer - García-Hernández, Eva Magdalena (2020)
Objective. The aim is to identify the differences between anxiety and depression according to contextual variables in women with breast cancer who are under treatment. Method. A comparative study was carried out in 91 women with breast cancer in three care units in Northeast Mexico. The Hospital Anxiety and Depression Scale were used. Results. The 51.6% (f = 47) resulted in anxiety and 25.3% (f = 23) depression. Anxiety and depression are not different according to the degree of schooling (p > .05) and marital status (p > .05). Depression (p = .001) and anxiety (p = 05) is different according to the unit of attention. In conclusion,it is important to take care of the emotional state of cancer patients since it was observed that half of the patients presented anxiety and a quarter with depression. It is necessary to analyze the context because depression and anxiety are different regarding the unit of attention.